Analisis Jaringan Komunikasi #Pilpres2024 Pada Platform Twitter - Alicia Laurence Efendi; Amira Fadilla; Arshilla Citra Khoirunnisa; Gema Nusantara Bakry; Nindi Aristi (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2023)
Toward the general election in 2024, discussions and political polemics in Indonesia are increasingly heated. This is also discussed through social media platforms, especially Twitter, which disseminates information widely and quickly so that more and more people know this information and share their opinions associated with the hashtag #Pilpres2024. This study aims to analyze the relations between actors (nodes) and social networks in terms of types of relationships, patterns of relations, and network relations of communication between actors, which are formed from the hashtag #Pilpres2024 from public participation on Twitter. This study uses the theory that is mostly used for network research, namely Graph Theory. The results of the research show that the social network design that is formed is the complete network design with 581 nodes and 320 edges. The type of relationship that is formed is a two-mode relationship type with a wheel communication pattern and a chain communication pattern. The communication network formed is directed and asymmetric. Based on the visualization results of this research, it can be concluded that the message can be conveyed effectively through the help of Twitter social media because it is carried out by various actors in it.